TRANSFORMASI PERMUKIMAN MASYARAKAT TRADISIONAL BATAK TOBA - Ria, Emmy; Ikaputra, . (ALUR :Jurnal Arsitektur, 2020)
Toba Batak traditional community settlements are much influenced by the main livelihood of the community namely farming. Matters relating to these livelihoods include water springs, forests and land. Besides that the factor that also influences is a very close kinship in the community. Kinship in patrilineal family relationships and in affina family relationships. These two things can be seen in the pattern of community settlements where there are facilities that are shared by the community both in relation to agricultural activities or in relations with kinship or traditional ceremonies. The development of community settlements can then be seen starting from the smallest scope, namely huta, then horja and bius. The development of huta, horja and bius is always related to the regulation of natural resources and traditional ceremonies. Changes to be discussed are changes related to the implementation of traditional ceremonies, regulation of the use of natural resources, defense and use of shared facilities. The wider the area of a settlement, the more complex the problems that occur. This is what we want to see in managing the traditional Batak Toba community settlements that have a very specific regulatory system